2018
DOI: 10.1016/j.jacc.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Smartwatch Algorithm for Automated Detection of Atrial Fibrillation

Abstract: The KB algorithm for AF detection supported by physician review can accurately differentiate AF from SR. This technology can help screen patients prior to elective CV and avoid unnecessary procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
281
3
11

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 384 publications
(300 citation statements)
references
References 13 publications
5
281
3
11
Order By: Relevance
“…Compared with 12 lead electrocardiograms interpreted by electrophysiologists, the automated algorithm was reported to have a sensitivity and specificity of 93% and 84%, respectively, in a small cross sectional study of patients with atrial fibrillation undergoing cardioversion (table 5). 68 It should be noted that about one third of the electrocardiograms were uninterpretable and excluded from this analysis.…”
Section: Newer Detection Methodsmentioning
confidence: 99%
“…Compared with 12 lead electrocardiograms interpreted by electrophysiologists, the automated algorithm was reported to have a sensitivity and specificity of 93% and 84%, respectively, in a small cross sectional study of patients with atrial fibrillation undergoing cardioversion (table 5). 68 It should be noted that about one third of the electrocardiograms were uninterpretable and excluded from this analysis.…”
Section: Newer Detection Methodsmentioning
confidence: 99%
“…Automated algorithms have demonstrated excellent accuracy in interpreting single‐lead ECG when compared with contemporaneous 12‐lead ECG as the reference standard (Table ). However, between 15 and 33% of the traces were deemed unclassified by the automated algorithm, with baseline artefact being the primary reason for this classification . Clinicians were able to interpret recordings deemed unclassified by the device, with 100% sensitivity and 80% specificity .…”
Section: Sensitivity and Specificity Of Smart Device Platforms (Sdp)mentioning
confidence: 99%
“…AliveCor's atrial fibrillation detection algorithm was shown to have a sensitivity and specificity of 96.6% and 94%, respectively, when used with the KardiaMobile . When used with the KardiaBand, the algorithm demonstrated a sensitivity and specificity of 93% and 84%, respectively . Another ECG example is the QardioCore .…”
Section: Four System Architectures Of Biosensors For Personal Mhealthmentioning
confidence: 99%